Tempo e memória na construção narrativa de Valter Hugo Mãe, em “a máquina de fazer espanhóis”: uma metáfora da última nau portuguesa - Louzeiro, Elias dos Reis (2018)
The present research aims to demonstrate the presence of multiple temporalities in the Valter Hugo Mãe’s novel a máquina de fazer espanhóis. Such temporalities operate in both sequential and memorialistic perspectives, in which action and recollection alternate throughout the narrative setting an interplay between past and present. The character interacts on a unstable and hesitant manner, in constant progression and retreat on emotional and personal conditions. And the character Portugal also demonstrates such oscillating characteristics. For both characters, the previous time is brought to the present throughout a nostalgic discourse and a refusal of action. Considering the theoretical background for analysis, the investigantions conducted by Paul Ricoeur (2012), Santo Agostinho (1999), Benedito Nunes (2010) and Terry Eagleton (2010), related to the concept of time; Henri Bergson (1990), Ecléa Bosi (2003) and Jeanne Marie Gagnebin (2006), with respect to the studies about memory; and also observing Eduardo Lourenço’s reflections (2004) on the grounding of the formation of the Lusitanian identity. The conclusion adresses that the novel attempts to emphasize paradoxal relations between life-death, action-stagnation, mythical time-present time, and that the unlikely relation examined in a senile atmosphere which conducts to a new life